Preparation method of welding yarn melt direct spinning composite filament and application of welding yarn melt direct spinning composite filament in fabric
Through the preparation method of welding yarn melt direct spinning composite filaments, the high-temperature melting function of low-melting point polyester material is used to solve the problem of deflation and hair removal and slipping of cloths such as plush and blankets, which improves the durability and user experience of fiber fabrics, while maintaining the feel and dyeing effect of the fabric.
Patent Information
- Application Number
- CN202410582695.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-04-29
AI Technical Summary
Plush, blankets and industrial cloth are prone to defoaming and hair removal and slipping problems after use, which affects the durability and user experience of the product.
By using the preparation method of melt-spun composite filaments with welding yarn, the melt-spun is directly spun by melt-spinning the low-melting point polyester material and the high-melting point polyester material in a specific ratio, a new composite filament fiber material with welding function is produced. During the weaving process, this material uses the high temperature melting of low-melting point polyester material to play a welding fixing role, solving the problems of defoiling, hair removal and slipping.
This method not only solves the problems of deflation and hair removal and slipping of cloths such as plush and blankets, improves the durability and user experience of fiber fabrics, but also ensures the feel of the fabric and the dyeing effect of the fabric, meeting the needs of different weaving fields.
Smart Images

Figure CN119900119A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fibers, in particular to a preparation method of welding yarn melt-spun composite filaments and application thereof in fabrics. Background Art
[0002] Polyester fiber has a wide range of applications, finding widespread use in both consumer and industrial sectors. Polyester fiber accounts for a significant portion of the production capacity of plush, blankets, and industrial fabrics. While these fabrics have greatly enriched people's lives, they often experience issues such as shedding, hair loss, and thread slippage, impacting product durability and customer experience, and remaining a persistent pain point and challenge in the industry. While improvements in weaving equipment and processes have resulted in some improvement, these issues remain largely unresolved.
[0003] In order to completely solve the difficulties and pain points of the industry, researchers started from the functional design of fiber materials, using the characteristics of different fiber materials, selecting special equipment for melt direct spinning continuous production such as polymerization and spinning, as well as related special additive preparation and addition equipment, to develop and produce a new composite filament fiber material with welding fiber material and backbone fiber material as one. This new composite filament fiber material has equally excellent weaving performance in the weaving process. In the fabric dyeing and finishing process, the high-temperature melting of the welding fiber material is used to weld and fix the composite filament backbone fiber material and the veil fiber material of the fabric. Through the design of the fiber ratio of welding fiber material and backbone fiber material, the above-mentioned plush, blanket and other fabrics do not affect the feel and dyeing effect of the cloth, while solving the problems of fabric shedding and slipping, giving the fiber fabric a new durable performance. Summary of the Invention
[0004] In order to completely solve the problems of shedding, hair removal, and thread slippage in fabrics such as plush, blankets, and industrial fabrics, and to increase the durability and user experience of textiles, the present invention provides a method for preparing a melt-spun composite filament from a welding yarn and its application in fabrics, producing a new composite filament fiber material that integrates a low-melting-point fiber material for welding and a backbone fiber material. By designing the fiber ratio of the low-melting-point fiber material for welding and the backbone fiber material, and utilizing the high-temperature melting of the low-melting-point fiber material for welding, the backbone fiber material of the composite filament and the veil fiber material of the fabric are welded and fixed, so that the feel and dyeing effect of fabrics such as plush and blankets are not affected, while solving the problems of shedding, hair removal, and thread slippage.
[0005] The purpose of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a melt-spun composite filament of a welding yarn, comprising the following steps: (1) terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, neopentyl glycol and a catalyst are mixed to form a slurry, and a low melting point polyester material is obtained by continuous esterification reaction and polycondensation reaction; (2) The low-melting-point polyester material and the high-melting-point polyester material are respectively transported to the spinning composite box in the form of melts, and after being measured according to the ratio, they are sent to the spinning assembly to spray out filaments A and filaments B, which are successively cooled, stretched, networked and wound to obtain welded yarn melt-spun composite filaments.
[0006] The composite filament production technology of this invention utilizes equipment selection based on the characteristics of different fiber materials, including specialized polymerization and spinning equipment, as well as equipment for preparing and adding specialized additives. This results in a new composite filament material that integrates a welding fiber material and a backbone fiber material. The welding fiber material is a low-melting-point polyester material that acts as a melt-welding and fixing agent between fibers or fabrics. The backbone fiber material is a high-melting-point polyester material with a melting point much higher than that of the welding fiber material. After the welding fiber material reaches its melting point and melts, the backbone fiber material remains below this point, providing support and maintaining the fabric's style and dimensional stability.
[0007] The present invention can calculate and control the metering pump frequencies for each of the A and B components, based on the yarn fineness specifications required by different fabrics, accurately measuring the melt output of the metering pumps to achieve the desired yarn component ratio. By controlling the yarn ratio and the stretching and shaping process, the composite filament produced can be applied to various downstream weaving applications, expanding the application range of composite filament welding yarns.
[0008] Low-melting-point polyester materials are synthesized by continuous esterification and polycondensation chemical reactions. They use polyester segments formed by the polymerization of terephthalic acid and ethylene glycol as the matrix, and add isophthalic acid (IPA), neopentyl glycol (NPG), and adipic acid (AA) as modifiers to achieve the purpose of lowering the melting point.
[0009] The addition of isophthalic acid (IPA) disrupts the regularity of the polyester macromolecular chain, reduces the interaction between the molecular segments, and makes the segments more mobile, thereby effectively lowering the melting point of the polyester. As the amount of IPA added increases, the melting point of the copolyester decreases in a linear relationship. Analysis of the crystallization mechanism shows that this is mainly due to the introduction of IPA into the molecular chain, which disrupts the regularity of the polyester molecular chain. The molecular chains require more activation energy to fit into the crystal lattice during crystallization. Crystallization can only occur at higher temperatures. This increase in crystallization temperature significantly reduces the polyester's ability to crystallize, resulting in imperfect crystallization and causing the formed crystals to melt at lower temperatures, which reduces the melting point.
[0010] The molecular structure of adipic acid (AA) is a linear carbon chain, making it relatively soft. When AA is added to the polymer, it joins the polymer as a main chain, increasing the length and number of carbon chains in the polyester, thereby softening the long polymer chain. This also disrupts the ordered structure of the polyester chain, significantly reducing the length of the polyester chain segments that can enter the crystal lattice, lowering crystallinity and ultimately lowering the polymer's melting point.
[0011] Low-melting-point polyester can be obtained by copolymerizing IPA and the dibasic acid AA. However, this low-melting-point polyester has a low glass transition temperature and softening temperature, and samples tend to clumping after storage for a period of time, creating inconveniences for its production, transportation, and downstream users. To resolve this contradiction, neopentyl glycol (NPG) was added. The presence of two symmetrical methyl groups in NPG increases the intermolecular distance within the polyester molecular structure, reducing intermolecular forces. It also hinders conformational rotation of the macromolecular chain segments, raising the softening point and glass transition temperature. Therefore, this modifier successfully resolves this contradiction and plays a key role in the preparation of low-melting-point polyester.
[0012] The low-melting-point polyester material in the present invention can play a welding role among different fiber materials. It can not only be used to weld and fix polyester fiber yarns, but also can be used to weld and fix natural fibers, regenerated fibers and other chemical fibers, as well as blended yarns.
[0013] Preferably, the molar ratio of terephthalic acid, isophthalic acid, adipic acid, ethylene glycol and neopentyl glycol is 50-80:20-50:5-20:80-110:20-50, and the ratio of the total molar amount of acid to the total molar amount of alcohol is 1:1.3.
[0014] Preferably, the added amount of the catalyst is 250 to 300 ppm based on the theoretical mass of the synthesized polyester calculated based on the total molar amount of the acid.
[0015] Preferably, the esterification reaction is as follows: under stirring, the first esterification reaction temperature is 220-235° C., the pressure is 0.5-0.7 MPa, until the acid value is detected to be 1000-1200 mol / t; then a second esterification reaction is carried out at a reaction temperature of 230-250° C., the pressure is 0.2-0.3 MPa, until the acid value is detected to be 400-600 mol / t.
[0016] In order to ensure that the materials react evenly and fully, the materials are stirred.
[0017] Preferably, during the esterification reaction, according to the matting requirements of the product, for example, 0.2-0.3% matting agent emulsion is added according to the mass ratio of the synthetic melt when producing a semi-matt product, and 2-3% matting agent emulsion can be added according to the mass ratio of the synthetic melt when producing a fully matt product.
[0018] Preferably, the polycondensation reaction is as follows: under stirring, a pre-polycondensation reaction is first carried out, the vacuum degree is reduced to an absolute pressure of 10-15 kPa, and the reaction temperature is 250-260°C; then a final polycondensation reaction is carried out, the vacuum degree is controlled at an absolute pressure of 200-500 Pa, and the reaction temperature is 260-270°C, until the intrinsic viscosity of the melt reaches 0.60-0.72 dL / g, and the discharge pump is sent to the spinning device.
[0019] In order to ensure that the materials react evenly and fully, the preliminary polycondensation reaction and the final polycondensation reaction are also carried out under stirring.
[0020] Preferably, the low-melting-point polyester material has a melting point of 89-140°C.
[0021] Preferably, the high melting point polyester material melt is prepared by subjecting high melting point polyester chips to the steps of conveying, crystallizing and drying, screw melting, and melt filtering to obtain the high melting point polyester material melt.
[0022] Preferably, the melting point of the high-melting-point polyester material melt is 258-262° C.; and the strength of the fiber obtained by spinning the high-melting-point polyester material melt is ≥3.8 cN / dtex.
[0023] The high-melting-point polyester material melt is obtained by crystallizing, drying and melting high-melting-point polyester chips. As the backbone fiber material, the polyester chips have a high melting point and the resulting fiber has high strength. In the weaving process, it can play a backbone supporting role and maintain the fabric style and dimensional stability.
[0024] Preferably, the moisture content of the chips of the high melting point polyester material after crystallization and drying is 20 to 80 ppm.
[0025] Preferably, in the composite filament, the mass ratio of filament A to filament B is 20-45%:55-80%, and the total mass percentage is 100%.
[0026] The fiber ratio design of the fiber material is based on the type of yarn required for the weight of each meter of the fabric, and the ratio of the fibers of component A and component B is designed to meet the weaving process and weight requirements, and at the same time, the yarns of the fabric can be welded and fixed in the finishing stage.
[0027] Preferably, the screw melting of the high melting point polyester chips is gradually melted at 265-295°C; further, the screw temperature is zone-controlled, which is beneficial to the melting, transportation and homogenization of the chips. The screw is divided into four temperature control zones. Zone one is used as the feeding zone, and the temperature is controlled at a lower level at 265-275°C to avoid screw ring knots affecting the feeding; Zones two and three are used as melting zones, and the temperatures are controlled at 275-290°C respectively; Zone four is used as the melting mixing and homogenization zone, and the temperature is controlled at 285-295°C to ensure that the materials are fully melted and evenly mixed.
[0028] Preferably, the melt is transported to the spinning composite box, accurately measured by respective metering pumps according to the yarn process ratio requirements, and sent to the spinneret assembly to spray out fiber filaments, which are cooled and formed by the annular air cooling device, and are respectively sent to the double-wire stretching and heat setting device, and the filaments A and B are combined by the network device and then wound into shape by the winding device to obtain welding yarn composite filaments for use in the downstream weaving process.
[0029] Preferably, the spinning temperature of the spinning composite beam is 280-290°C.
[0030] Preferably, the temperature of the cooling air is 20-22° C., and the humidity is 80-95%.
[0031] The process requires that the temperature and humidity of the cooling air must be maintained within a certain stable range to prevent temperature and humidity fluctuations from affecting the internal quality stability of the yarn, thereby affecting yarn dyeing and breaking yarns.
[0032] Preferably, the filament B is stretched by hot roller stretching, the temperature of the first hot roller is 70-85°C, the stretching speed is 1200-1600 m / min, the temperature of the second hot roller is 120-135°C, the stretching speed is 3500-4200 m / min, and the stretching ratio is 1.8-2.7 times.
[0033] Preferably, the yarn A is stretched by roller traction, the speed of the first roller is 5 to 20 m / min lower than that of the second roller, and the speed of the second roller is synchronized with the stretching speed of the second hot roller of the yarn B, and the speed is 3500 to 4200 m / min.
[0034] The yarns A and B are stretched using different processes, and then twisted together through a network device and wound up to form a welding yarn composite filament. This ensures that both the yarns A and B have good mechanical properties, and the two are better matched when twisted together. The resulting welding yarn also has better bonding and weaving properties.
[0035] Preferably, the composite filament has a breaking strength of 3.8 to 4.1 cN / dtex and an elongation at break of 22 to 30%.
[0036] In the second aspect, the present invention also provides an application of a composite filament in a fabric, comprising the following steps: the fabric is a three-shuttle yarn (face yarn, middle yarn, bottom yarn) or a two-shuttle yarn (face yarn, bottom yarn), and the composite filament is used as a middle yarn or bottom yarn in weaving. In the fabric dyeing or finishing process, the dyeing or finishing temperature is controlled to be not lower than the melting point of the low-melting-point polyester material in the composite filament, so that the low-melting-point polyester material melts and thus plays a welding and fixing role.
[0037] Utilizing the different functions of the face yarn, middle yarn, and ground yarn in fabrics such as plush and blankets, the new composite filament fiber material produced by this invention is used as the middle yarn or ground yarn. During dyeing or finishing, the low-melting-point polyester material in the composite filament is melted at high temperature. Due to the interlaced yarn structure in the fabric, the melted low-melting-point polyester material fully contacts the face yarn, middle yarn, and ground yarn of the fabric, resulting in numerous contact points and thus forming an effective welding and fixing effect. The composite filament is a twisted tow, and the B component in the tow is a high-melting-point polyester material. The fiber has a high melting point, strength, elongation, and dimensional stability, which can meet the needs of the smooth weaving process and play a supporting role in the application of the middle yarn and ground yarn.
[0038] The composite filaments of the present invention do not affect the dyeing effect and appearance and style of the fabric. During the finishing or dyeing process, the temperature of the fabric is controlled to be higher than the melting point of component A, but far lower than the melting point of component B fiber material and veil fiber material, thereby achieving melting of the low-melting-point polyester material. After cooling, the low-melting-point polyester material serves as a welded connection between the fabric veil, middle yarn, and base yarn, while the performance of component B fiber material and the veil and base yarn fibers remains unchanged. Therefore, the fabric retains its original dyeing effect and appearance and style. The use of the welded yarn composite filaments of the present invention does not affect the original feel and dyeing effect of fabrics such as plush and blankets, while simultaneously solving problems such as shedding and thread slippage.
[0039] Relative to the composite yarn of the sheath-core structure, the cortex is a low-melting-point fiber material and the core is a high-melting-point fiber material. It is impossible to fully stretch and heat-set during the spinning process, does not have dimensional stability, cannot meet the downstream filament weaving needs, and can only be used as short fibers and melt-blown cloth fields. The present invention selects and is equipped with special stretching and heat-setting equipment, and utilizes the welding yarn composite filament fiber produced by the twisted tow structure to have higher dimensional stability and strength and elongation, which can meet the downstream filament weaving needs. The welding yarn composite filament manufacturing method of the present invention is more able to play the role of different materials in fiber applications, is more suitable for filament spinning production, and the fiber ratio and specification thickness are controllable. According to the downstream weaving needs, the AB components can be freely matched, which greatly meets the weaving needs of different downstream fields.
[0040] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes isophthalic acid (IPA), neopentyl glycol (NPG), and adipic acid (AA) as modifiers to produce a low-melting-point polyester material. By studying the reaction mechanism and optimizing the molar ratio of the different materials, the present invention overcomes the problems of low glass transition temperature and softening temperature of the low-melting-point polyester, which leads to the sticking of the sample after storage for a period of time. The glass transition temperature of the low-melting-point polyester produced by the present invention is 62-74°C, which is close to the glass transition temperature (80°C) of conventional polyester chips.
[0041] (2) The present invention adopts melt direct spinning continuous polymerization production technology to produce composite fiber filaments. After process optimization and molar ratio adjustment, composite filaments of AB component fiber materials with different melting points can be produced according to the finishing requirements of fabrics, meeting the needs of different customers for different finishing temperature conditions.
[0042] (3) The composite filaments of the present invention can be applied to various downstream weaving fields. They can be used not only to weld polyester fiber yarns, but also to weld natural fibers, other chemical fibers, and blended yarns. They are particularly suitable for fabrics such as plush and blankets. They ensure stable quality and uniform welding of the fabric without affecting the feel of the fabric and the dyeing effect of the fabric. They also solve problems such as shedding and thread slippage. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a schematic diagram of the melt direct spinning composite filament process; Figure 2 This is a schematic diagram of the connection of the composite filament double-wire stretching and shaping device; Figure 3 Schematic diagram of the spinning composite box device.
[0044] The reference numerals are: oiling device 1, roller 2, hot roller 3, network device 4, winding device 5. DETAILED DESCRIPTION
[0045] The technical solutions of the present invention are described below with specific embodiments, but the protection scope of the present invention is not limited thereto: Example 1 like Figure 1 The figure shows the process diagram of melt direct spinning composite filament, and the specific steps are as follows: (1) Terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, and neopentyl glycol were mixed in a molar ratio of 60:30:10:90:40, with a total molar ratio of acid to alcohol of 1:1.3. The mixture was stirred evenly in a slurry mixing kettle to form a slurry. Sb2O3 catalyst was added during stirring at a ratio of 250 ppm of the molar amount of the acid substances (terephthalic acid, isophthalic acid, and adipic acid) to the theoretical mass of the synthesized polyester. The resulting slurry was pumped into a first esterification reactor. Under stirring, the first esterification reaction temperature was controlled at 230°C and the pressure was 0.6 MPa until the acid value was detected to be 1100±100 mol / t. The slurry was then transferred to a second esterification reactor and the reaction temperature was controlled at 242°C and the pressure was 0.2 MPa for further esterification reaction until the acid value was detected to be 500±100 mol / t. The fully esterified slurry was transferred to a pre-polycondensation reactor. While stirring, the vacuum level was reduced to 12 kPa absolute, and the pre-polycondensation temperature was controlled at 255°C. Reaction byproducts were gradually pumped out of the system under a low vacuum to promote the forward progress of the polycondensation reaction. The pre-polycondensation reactants were then transferred to a final polycondensation reactor via a melt pump. Further vacuum was applied to the final polycondensation reactor, where the vacuum level was controlled at 300 Pa absolute and the reaction temperature was 270°C. Based on the stirring current and system viscosity data of the final polycondensation reactor, as well as sampling and testing results, the reaction conditions and times for the pre-polycondensation and final polycondensation were optimized, ultimately yielding a low-melting-point polyester material with an intrinsic viscosity of 0.72 dL / g, a melting point of 95°C, and a glass transition temperature of 62°C. The low-melting-point polyester melt, serving as component A, was transferred to the spinning beam via a melt booster pump.
[0046] (2) High melting point polyester chips (melting point 259℃) are fed to a high-level silo. The chip discharge amount is calculated based on the output. The crystallization temperature is controlled at 160℃ and the drying air volume is controlled. The chips are fully crystallized in the crystallization bed and the water content of the chips is removed. After crystallization, the chips enter the drying tower. The temperature of the drying tower is controlled at 175℃ and the drying air volume is controlled to further remove the water content of the chips. The material level of the drying tower is controlled to ensure that the chip drying time is 4 hours or more, and dry chips with a moisture content of 50ppm are obtained. The dried chips are melted by a screw, and the temperature of the four zones is controlled at 272℃, 278℃, 285℃, and 290℃ respectively. The chip impurities and gel particles in the melt are filtered out by a 20-40μm melt filter to obtain the high melting point polyester material melt of component B and send it to the spinning composite box.
[0047] (3) With the goal of producing 167dtex / 72f welding yarn composite filaments, the ratio of the total mass of filament A to the total mass of filament B (i.e., the ratio of the melt supply of component A to component B) is 2:3. The frequency and speed of each metering pump are calculated to accurately measure the melt supply. According to the material properties of component AB and the flow curve in the molten state, the spinning temperature of the spinning composite box is optimized and adjusted to 285℃. Figure 3The figure shows a schematic diagram of the device of the spinning composite box. The yarns A and B are ejected from the spinning assembly and passed through the annular air cooling device. The air temperature is controlled at 20°C, the humidity is 85%, and the air pressure is 40 Pa. The yarns are uniformly cooled and formed. After the spinning oiling device 1, the yarn A is sent to the first and second yarn rollers 2. The speeds of the first and second yarn rollers are controlled at 4190m / min and 4200m / min respectively. The yarn B is sent to the hot roller 3 for stretching. The temperature of the first hot roller is 85°C and the speed is 1550m / min. The temperature of the second hot roller is 130°C and the speed is 4200m / min. The stretching ratio is 2.71 times. Figure 2 The figure shows the connection diagram of the double-wire stretching and shaping device for composite filaments; the AB filaments are combined into strands through the network device 4 and then wound into shape through the winding device 5, thereby obtaining a finished welded yarn composite filament.
[0048] Example 2 (1) Terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, and neopentyl glycol were mixed in a molar ratio of 65:25:10:95:35, with a total molar ratio of acid to alcohol of 1:1.3. The mixture was stirred evenly in a slurry mixing kettle to form a slurry. Sb2O3 catalyst was added during stirring. The catalyst ratio was 250 ppm based on the molar amount of the acid substances (terephthalic acid, isophthalic acid, and adipic acid) relative to the theoretical mass of the synthesized polyester. The resulting slurry was pumped into a first esterification reactor. Under stirring, the first esterification reaction temperature was controlled at 230°C and the pressure was 0.6 MPa until the acid value was detected to be 1100±100 mol / t. The slurry was then transferred to a second esterification reactor and the reaction temperature was controlled at 242°C and the pressure was 0.2 MPa for further esterification reaction until the acid value was detected to be 500±100 mol / t. The fully esterified slurry was transferred to a pre-polycondensation reactor. While stirring, the vacuum level was reduced to 12 kPa absolute, and the pre-polycondensation temperature was controlled at 255°C. Reaction byproducts were gradually pumped out of the system under low vacuum to promote the forward progress of the polycondensation reaction. The pre-polycondensation reactants were then transferred to a final polycondensation reactor via a melt pump. Further vacuum was applied to the final polycondensation reactor, where the vacuum level was controlled at 300 Pa absolute and the reaction temperature was 270°C. Based on the stirring current and system viscosity data of the final polycondensation reactor, as well as sampling and testing results, the reaction conditions and times for the pre-polycondensation and final polycondensation were optimized, ultimately yielding a low-melting-point polyester material with an intrinsic viscosity of 0.69 dL / g, a melting point of 102°C, and a glass transition temperature of 65°C. The low-melting-point polyester melt, serving as component A, was transferred to the spinning beam via a melt booster pump.
[0049] (2) High melting point polyester chips (melting point 259℃) are fed to a high-level silo. The chip discharge amount is calculated based on the output. The crystallization temperature is controlled at 160℃ and the drying air volume is controlled. The chips are fully crystallized in the crystallization bed and the water content of the chips is removed. After crystallization, the chips enter the drying tower. The temperature of the drying tower is controlled at 175℃ and the drying air volume is controlled to further remove the water content of the chips. The material level of the drying tower is controlled to ensure that the chip drying time is 4 hours or more, and dry chips with a moisture content of 50ppm are obtained. The dried chips are melted by a screw, and the temperature of the four zones is controlled at 272℃, 278℃, 285℃, and 290℃ respectively. The chip impurities and gel particles in the melt are filtered out by a 20-40μm melt filter to obtain the high melting point polyester material melt of component B and send it to the spinning composite box.
[0050] (3) With the goal of producing 167dtex / 72f welding yarn composite filament varieties, the ratio of the total mass of filament A to the total mass of filament B (i.e., the ratio of the melt supply of component A to component B) is 2:3, and the frequency and speed of each metering pump are calculated to accurately measure the melt supply. According to the material properties of the AB components and the flow curve in the molten state, the spinning temperature of the spinning composite box is optimized and adjusted to 285°C, and the filaments A and B are sprayed out through the spinneret assembly. The filaments are cooled and formed uniformly through the ring-blown cooling device with the air temperature controlled at 20°C, the air humidity at 85%, and the air pressure at 40 Pa. After passing through the oiling device, the filaments A are sent to the first and second guide rollers, and the speeds of the first and second guide rollers are controlled at 4190 m / min and 4200 m / min, respectively. The filaments B are sent to hot rollers for stretching. The temperature of the first hot roller is 85°C and the speed is 1550 m / min, and the temperature of the second hot roller is 130°C and the speed is 4200 m / min, with a stretching ratio of 2.71 times. The AB filaments are combined through the network device and then wound into shape through the winding device, thereby obtaining a finished welding yarn composite filament.
[0051] Example 3 (1) Terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, and neopentyl glycol were mixed in a molar ratio of 70:20:10:100:30, with a total molar ratio of acid to alcohol of 1:1.3. The mixture was stirred evenly in a slurry mixing kettle to form a slurry. Sb2O3 catalyst was added during stirring at a ratio of 250 ppm of the molar amount of the acid substances (terephthalic acid, isophthalic acid, and adipic acid) to the theoretical mass of the synthesized polyester. The resulting slurry was pumped into a first esterification reactor. Under stirring, the first esterification reaction temperature was controlled at 230°C and the pressure was 0.6 MPa until the acid value was detected to be 1100±100 mol / t. The slurry was then transferred to a second esterification reactor and the reaction temperature was controlled at 242°C and the pressure was 0.2 MPa for further esterification reaction until the acid value was detected to be 500±100 mol / t. The fully esterified slurry was transferred to a pre-polycondensation reactor. While stirring, the vacuum level was reduced to 12 kPa absolute, and the pre-polycondensation temperature was controlled at 255°C. Reaction byproducts were gradually pumped out of the system under low vacuum to promote the forward progress of the polycondensation reaction. The pre-polycondensation reactants were then transferred to a final polycondensation reactor via a melt pump. Further vacuum was applied to the final polycondensation reactor, where the vacuum level was controlled at 300 Pa absolute and the reaction temperature was 270°C. Based on the stirring current and system viscosity data of the final polycondensation reactor, as well as sampling and testing results, the reaction conditions and times for the pre-polycondensation and final polycondensation were optimized, ultimately yielding a low-melting-point polyester material with an intrinsic viscosity of 0.67 dL / g, a melting point of 114°C, and a glass transition temperature of 69°C. The low-melting-point polyester melt, serving as component A, was transferred to the spinning beam via a melt booster pump.
[0052] (2) High melting point polyester chips (melting point 259℃) are fed to a high-level silo. The chip discharge amount is calculated based on the output. The crystallization temperature is controlled at 160℃ and the drying air volume is controlled. The chips are fully crystallized in the crystallization bed and the water content of the chips is removed. After crystallization, the chips enter the drying tower. The temperature of the drying tower is controlled at 175℃ and the drying air volume is controlled to further remove the water content of the chips. The material level of the drying tower is controlled to ensure that the chip drying time is 4 hours or more, and dry chips with a moisture content of 50ppm are obtained. The dried chips are melted by a screw, and the temperature of the four zones is controlled at 272℃, 278℃, 285℃, and 290℃ respectively. The chip impurities and gel particles in the melt are filtered out by a 20-40μm melt filter to obtain the high melting point polyester material melt of component B and send it to the spinning composite box.
[0053] (3) With the goal of producing 167dtex / 72f welding yarn composite filament varieties, the ratio of the total mass of filament A to the total mass of filament B (i.e., the ratio of the melt supply of component A to component B) is 2:3, and the frequency and speed of each metering pump are calculated to accurately measure the melt supply. According to the material properties of the AB components and the flow curve in the molten state, the spinning temperature of the spinning composite box is optimized and adjusted to 285°C, and the filaments A and B are sprayed out through the spinneret assembly. The filaments are cooled and formed uniformly through the ring-blown cooling device with the air temperature controlled at 20°C, the air humidity at 85%, and the air pressure at 40 Pa. After the oiling device, the filaments A are sent to the first and second guide rollers, and the speeds of the first and second guide rollers are controlled at 4190 m / min and 4200 m / min, respectively. The filaments B are sent to hot rollers for stretching. The temperature of the first hot roller is 85°C and the speed is 1550 m / min, and the temperature of the second hot roller is 130°C and the speed is 4200 m / min, with a stretching ratio of 2.71 times. The AB filaments are combined through the network device and then wound into shape through the winding device, thereby obtaining a finished welding yarn composite filament.
[0054] Example 4 (1) Terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, and neopentyl glycol were mixed in a molar ratio of 75:15:10:110:20, with a total molar ratio of acid to alcohol of 1:1.3. The mixture was stirred evenly in a slurry mixing kettle to form a slurry. Sb2O3 catalyst was added during stirring at a ratio of 250 ppm of the molar amount of the acid substances (terephthalic acid, isophthalic acid, and adipic acid) to the theoretical mass of the synthesized polyester. The resulting slurry was pumped into a first esterification reactor. Under stirring, the first esterification reaction temperature was controlled at 230°C and the pressure was 0.6 MPa until the acid value was detected to be 1100±100 mol / t. The slurry was then transferred to a second esterification reactor and the reaction temperature was controlled at 242°C and the pressure was 0.2 MPa for further esterification reaction until the acid value was detected to be 500±100 mol / t. The fully esterified slurry was transferred to a pre-polycondensation reactor. While stirring, the vacuum level was reduced to 12 kPa absolute, and the pre-polycondensation temperature was controlled at 255°C. Reaction byproducts were gradually pumped out of the system under low vacuum to promote the forward progress of the polycondensation reaction. The pre-polycondensation reactants were then transferred to a final polycondensation reactor via a melt pump. Further vacuum was applied to the final polycondensation reactor, where the vacuum level was controlled at 300 Pa absolute and the reaction temperature was 270°C. Based on the stirring current and system viscosity data of the final polycondensation reactor, as well as sampling and testing results, the reaction conditions and times for the pre-polycondensation and final polycondensation were optimized, ultimately yielding a low-melting-point polyester material with an intrinsic viscosity of 0.65 dL / g, a melting point of 132°C, and a glass transition temperature of 71°C. The low-melting-point polyester melt, serving as component A, was transferred to the spinning beam via a melt booster pump.
[0055] (2) High melting point polyester chips (melting point 259℃) are fed to a high-level silo. The chip discharge amount is calculated based on the output. The crystallization temperature is controlled at 160℃ and the drying air volume is controlled. The chips are fully crystallized in the crystallization bed and the water content of the chips is removed. After crystallization, the chips enter the drying tower. The temperature of the drying tower is controlled at 175℃ and the drying air volume is controlled to further remove the water content of the chips. The material level of the drying tower is controlled to ensure that the chip drying time is 4 hours or more, and dry chips with a moisture content of 50ppm are obtained. The dried chips are melted by a screw, and the temperature of the four zones is controlled at 272℃, 278℃, 285℃, and 290℃ respectively. The chip impurities and gel particles in the melt are filtered out by a 20-40μm melt filter to obtain the high melting point polyester material melt of component B and send it to the spinning composite box.
[0056] (3) With the goal of producing 167dtex / 72f welding yarn composite filament varieties, the ratio of the total mass of filament A to the total mass of filament B (i.e., the ratio of the melt supply of component A to component B) is 2:3, and the frequency and speed of each metering pump are calculated to accurately measure the melt supply. According to the material properties of the AB components and the flow curve in the molten state, the spinning temperature of the spinning composite box is optimized and adjusted to 285°C, and the filaments A and B are sprayed out through the spinneret assembly. The filaments are cooled and formed uniformly through the ring-blown cooling device with the air temperature controlled at 20°C, the air humidity at 85%, and the air pressure at 40 Pa. After passing through the oiling device, the filaments A are sent to the first and second guide rollers, and the speeds of the first and second guide rollers are controlled at 4190 m / min and 4200 m / min, respectively. The filaments B are sent to hot rollers for stretching. The temperature of the first hot roller is 85°C and the speed is 1550 m / min, and the temperature of the second hot roller is 130°C and the speed is 4200 m / min, with a stretching ratio of 2.71 times. The AB filaments are combined through the network device and then wound into shape through the winding device, thereby obtaining a finished welding yarn composite filament.
[0057] Example 5 The difference from Example 3 is that the 83 dtex / 48 f welding yarn is produced, and the ratio of the total mass of the filaments A to the total mass of the filaments B is 3:7.
[0058] With the goal of producing 83dtex / 48f welding yarn composite filament varieties, the ratio of the total mass of filament A to the total mass of filament B (that is, the ratio of the melt supply of component A and component B) is 3:7. The frequency and speed of each metering pump are calculated to accurately measure the melt supply. According to the material properties of the AB components and the flow curve in the molten state, the spinning temperature of the spinning composite box is optimized and adjusted to 285°C, and the filaments A and B are sprayed out through the spinneret assembly. The filaments are cooled and formed uniformly through the ring-blown cooling device with the air temperature controlled at 22°C, the air humidity at 85%, and the air pressure at 25 Pa. After passing through the oiling device, the filaments A are sent to the first and second guide rollers, and the speeds of the first and second guide rollers are controlled at 3745 m / min and 3750 m / min, respectively. The filaments B are sent to hot rollers for stretching. The temperature of the first hot roller is 80°C and the speed is 1420 m / min, and the temperature of the second hot roller is 126°C and the speed is 3750 m / min, with a stretching ratio of 2.64 times. The AB filaments are combined through the network device and then wound into shape through the winding device, thereby obtaining a finished welding yarn composite filament.
[0059] Example 6 The difference from Example 3 is that a 66 dtex / 36f welding yarn is produced, and the ratio of the total mass of the filaments A to the total mass of the filaments B is 3:7.
[0060] With the goal of producing 66dtex / 36f welding yarn composite filament varieties, the ratio of the total mass of filament A to the total mass of filament B (that is, the ratio of the melt supply of component A and component B) is 3:7. The frequency and speed of each metering pump are calculated to accurately measure the melt supply. According to the material properties of the AB components and the flow curve in the molten state, the spinning temperature of the spinning composite box is optimized and adjusted to 285°C, and the filaments A and B are sprayed out through the spinneret assembly. The filaments are cooled and formed uniformly through the ring-blown cooling device with the air temperature controlled at 22°C, the air humidity at 85%, and the air pressure at 20 Pa. After passing through the oiling device, the filaments A are sent to the first and second guide rollers, and the speeds of the first and second guide rollers are controlled at 3545 m / min and 3550 m / min, respectively. The filaments B are sent to hot rollers for stretching. The temperature of the first hot roller is 72°C and the speed is 1340 m / min, and the temperature of the second hot roller is 122°C and the speed is 3550 m / min, with a stretching ratio of 2.65 times. The AB filaments are combined through the network device and then wound into shape through the winding device, thereby obtaining a finished welding yarn composite filament.
[0061] Comparative Example 1 The difference from Example 3 is that no neopentyl glycol is added during the preparation of the low-melting-point polyester material.
[0062] Terephthalic acid, isophthalic acid, adipic acid, and ethylene glycol were mixed in a molar ratio of 70:20:10:130, with a total molar ratio of acid to alcohol of 1:1.3. The mixture was stirred uniformly in a slurry mixing kettle to form a slurry. During stirring, a Sb2O3 catalyst was added at a ratio of 250 ppm based on the molar amounts of the acids (terephthalic acid, isophthalic acid, and adipic acid) relative to the theoretical mass of the synthesized polyester. The resulting slurry was pumped to a first esterification reactor, where the reaction temperature was controlled at 230°C and the pressure was 0.6 MPa while stirring, until the acid value reached 1100±100 mol / t. The slurry was then transferred to a second esterification reactor where the reaction temperature was controlled at 242°C and the pressure was 0.2 MPa, where further esterification reactions were carried out until the acid value reached 500±100 mol / t. The fully esterified slurry was transferred to a pre-polycondensation reactor. While stirring, the vacuum level was reduced to 12 kPa absolute, and the pre-polycondensation temperature was controlled at 255°C. Reaction byproducts were gradually pumped out of the system under a low vacuum to promote the forward progress of the polycondensation reaction. The pre-polycondensation reactants were then transferred to a final polycondensation reactor via a melt pump. Further vacuum was applied to the final polycondensation reactor, where the vacuum level was controlled at 300 Pa absolute and the reaction temperature was 270°C. Based on the stirring current and system viscosity data of the final polycondensation reactor, as well as sampling and testing results, the reaction conditions and times for the pre-polycondensation and final polycondensation were optimized, ultimately yielding a low-melting-point polyester material with an intrinsic viscosity of 0.63 dL / g, a melting point of 152°C, and a glass transition temperature of 57°C. The low-melting-point polyester melt, serving as component A, was transferred to the spinning beam via a melt booster pump.
[0063] Comparative Example 2 The difference from Example 3 is that during the preparation of the low-melting-point polyester material, neopentyl glycol is replaced by 2,3-pentanediol.
[0064] Terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, and 2,3-pentanediol were mixed in a molar ratio of 70:20:10:100:30, with a total molar ratio of acid to alcohol of 1:1.3. The mixture was stirred evenly in a slurry mixing kettle to form a slurry. During stirring, Sb2O3 catalyst was added at a ratio of 250 ppm based on the molar amount of acid based on the theoretical mass of the synthesized polyester. The resulting slurry was pumped to a first esterification reactor, where the reaction temperature was controlled at 230°C and a pressure of 0.6 MPa while stirring, until the acid value reached 1100±100 mol / t. The slurry was then transferred to a second esterification reactor, where the reaction temperature was controlled at 242°C and a pressure of 0.2 MPa, for further esterification until the acid value reached 500±100 mol / t. The fully esterified slurry was transferred to a pre-polycondensation reactor. While stirring, the vacuum level was reduced to 12 kPa absolute, and the pre-polycondensation temperature was controlled at 255°C. Reaction byproducts were gradually pumped out of the system under a low vacuum to promote the forward progress of the polycondensation reaction. The pre-polycondensation reactants were then transferred to a final polycondensation reactor via a melt pump. Further vacuum was applied to the final polycondensation reactor, where the vacuum level was controlled at 300 Pa absolute and the reaction temperature was 270°C. Based on the stirring current and system viscosity data of the final polycondensation reactor, as well as sampling and testing results, the reaction conditions and times for the pre-polycondensation and final polycondensation were optimized, ultimately yielding a low-melting-point polyester material with an intrinsic viscosity of 0.62 dL / g, a melting point of 148°C, and a glass transition temperature of 51°C. The low-melting-point polyester melt, serving as component A, was transferred to the spinning beam via a melt booster pump.
[0065] Application Examples Taking the welding yarn composite filament finished product weaving three-shuttle yarn plush fabric (face yarn, middle yarn, bottom yarn) as an example, the welding yarn composite filament finished product prepared in Example 3 (the melting point of the low-melting point polyester material is 114°C) is used as the middle yarn in the weaving process, and the woven grey cloth is subjected to the napping and cutting process, and then dyed and heat-set (i.e., the finishing process), and the heat-setting temperature is 120±2°C.
[0066] Because the B component in the composite filament has the same strength and elongation as ordinary polyester fibers, good weaving performance is guaranteed during the weaving process. The middle yarn is twisted and interwoven with the face yarn and the bottom yarn as the knitting needles reciprocate, and is in full contact. In the heat setting process of the fabric, a certain pre-tension is given to the fabric. When the fabric is in a tense state, the setting temperature is controlled to be no lower than the melting point of the low-melting-point polyester material of component A in the composite filament, so that the low-melting-point polyester material melts, and multiple melting welding points are formed at the contact points with the face yarn and the bottom yarn. After the fabric cools, these welding points play a role in firmly welding and fixing the face yarn and the bottom yarn. The high-melting-point fiber material as the backbone of component B and the fiber materials of the face yarn and the bottom yarn are far below their melting temperature under this setting temperature condition. The yarn performance will not be affected or changed, and the appearance style and dyeing performance of the fabric will not be affected. The use of the welding yarn composite filament of the present invention not only keeps the appearance style and dyeing performance of the fabric unaffected, but also solves the problems of depilation and thread slippage of the fabric.
[0067] Table 1 As shown in Table 1, the low-melting-point polyester material prepared in the present invention also has a relatively high glass transition temperature, which can avoid the sticking phenomenon that occurs after the sample is stored for a long time. The composite filaments made from AB component fiber materials with different melting points can be applied to different downstream weaving fields to play a welding and fixing role between fiber yarns.
[0068] No neopentyl glycol was added to Comparative Example 1, and the glass transition temperature and softening point temperature of the resulting low-melting polyester material were significantly lower than those of Example 3. The difference between Comparative Example 2 and Example 3 is that neopentyl glycol was replaced with 2,3-pentanediol. 2,3-pentanediol and ethylene glycol are both two-carbon chain structures in the polyester molecular structure, and their functions and performances are basically similar. However, it is not necessarily the case that the glass transition temperature Tg will increase as the volume of the substituted side groups increases. The side groups of 2,3-pentanediol in the polyester molecular structure are flexible carbon chains. The presence of flexible side groups is equivalent to playing the role of a plasticizer, which has little effect on improving the softening point and glass transition temperature. The presence of two symmetrical methyl groups in neopentyl glycol increases the distance between molecules in the polyester molecular structure, reduces the intermolecular forces, and also hinders the conformational rotation of the macromolecular chain segments, which can improve the softening point and glass transition temperature.
[0069] The above are only preferred embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the description of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a melt-spun composite filament of a welding yarn, characterized in that: The steps include: (1) terephthalic acid, isophthalic acid, adipic acid, ethylene glycol, neopentyl glycol and a catalyst are mixed to form a slurry, and a low melting point polyester material is obtained by continuous esterification reaction and polycondensation reaction; (2) The low-melting-point polyester material and the high-melting-point polyester material are respectively transported to the spinning composite box in the form of melts, and after being measured according to the ratio, they are sent to the spinneret assembly to spray out filaments A and filaments B, which are successively cooled, stretched, networked and wound to obtain the melt-spun composite filaments of the welding yarn.
2. The method for preparing the melt-spun composite filament of welding yarn according to claim 1, characterized in that: The molar ratio of terephthalic acid, isophthalic acid, adipic acid, ethylene glycol and neopentyl glycol is 50-80:20-50:5-20:80-110:20-50, and the ratio of the total molar amount of acid to the total molar amount of alcohol is 1:1.
3.
3. The method for preparing the melt-spun composite filament of welding yarn according to claim 1, characterized in that: The amount of the catalyst added is 250-300 ppm based on the theoretical mass of the synthesized polyester calculated based on the total molar amount of the acid.
4. The method for preparing the melt-spun composite filament of welding yarn according to any one of claims 1 to 3, characterized in that: The esterification reaction is as follows: under stirring, the first esterification reaction temperature is 220-235° C. and the pressure is 0.5-0.7 MPa, and then the second esterification reaction is carried out at a reaction temperature of 230-250° C. and a pressure of 0.2-0.3 MPa.
5. The method for preparing the melt-spinning composite filament of welding yarn according to any one of claims 1 to 3, characterized in that: The polycondensation reaction is as follows: under stirring, a preliminary polycondensation reaction is first carried out, the vacuum degree is reduced to an absolute pressure of 10-15 KPa, and the temperature is 250-260° C.; and then a final polycondensation reaction is carried out, the vacuum degree is controlled at an absolute pressure of 200-500 Pa, and the temperature is 260-270° C., until the intrinsic viscosity of the melt reaches 0.60-0.72 dL / g.
6. The method for preparing the melt-spun composite filament of welding yarn according to claim 1, characterized in that: The melting point of the low-melting-point polyester material is 89-140°C; the melting point of the high-melting-point polyester material melt is 258-262°C.
7. The method for preparing the melt-spun composite filament of welding yarn according to claim 1 or 6, characterized in that: In the composite filament, the mass ratio of filament A to filament B is 20-45%:55-80%, and the total mass percentage is 100%.
8. The method for preparing the melt-spun composite filament of welding yarn according to claim 1, characterized in that: The cooling temperature is 20-22° C. and the humidity is 80-95%.
9. The method for preparing the melt-spun composite filament of welding yarn according to claim 1 or 8, characterized in that: The wire A is stretched by roller traction, the speed of the first roller is 5~20m / min lower than that of the second roller, and the speed of the second roller is synchronized with the stretching speed of the second hot roller of the wire B; the wire B is stretched by hot roller stretching, the temperature of the first hot roller is 70~85℃, the stretching speed is 1200~1600 m / min, the temperature of the second hot roller is 120~135℃, the stretching speed is 3500~4200 m / min, and the stretching multiple is 1.8~2.7 times.
10. An application of the melt-spun composite filament of welding yarn prepared by the preparation method according to any one of claims 1 to 9 in fabrics, characterized in that: The method comprises the following steps: the fabric is three-shuttle yarn or two-shuttle yarn, the composite filament is used as middle yarn or bottom yarn in the weaving process, and in the dyeing or finishing stage of the fabric, the dyeing or finishing temperature is controlled to be not lower than the melting point of the low-melting-point polyester material in the composite filament, so that the low-melting-point polyester material is melted to play a welding and fixing role.
Citation Information
Patent Citations
Preparation method of low-melting-point high-strength dacron composite monofilament
CN102797063A
Manufacture method for flexible bulletproof laminated plate
CN105196674A
Composite hot sticking fiber and preparation method thereof
CN106521748A
Hot-melt yarn fixation method for PET tatting textiles
CN108796824A
Preparation of low-melting-point polyester fiber and application of low-melting-point polyester fiber in natural fiber bonding
CN114262954A